2016
DOI: 10.1016/j.foodchem.2016.05.080
|View full text |Cite
|
Sign up to set email alerts
|

New integrative computational approaches unveil the Saccharomyces cerevisiae pheno-metabolomic fermentative profile and allow strain selection for winemaking

Abstract: During must fermentation by Saccharomyces cerevisiae strains thousands of volatile aroma compounds are formed. The objective of the present work was to adapt computational approaches to analyze pheno-metabolomic diversity of a S. cerevisiae strain collection with different origins. Phenotypic and genetic characterization together with individual must fermentations were performed, and metabolites relevant to aromatic profiles were determined. Experimental results were projected onto a common coordinates system,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…These authors concluded that commercial wine strains are characterized by high biomass concentration and good fermentative performance, low acetate production, and low ethyl butyrate synthesis. More recently, and similar to the work presented here for S. cerevisiae mezcal strains, Franco-Duarte et al [12] established that, for their 24 S. cerevisiae strains, ethanol and organic acids (in particular acetic acid) concentration explained most of the metabolic differences among strains. The S. cerevisiae strains studied in more detail here produce comparable amounts of ethanol as the commercial strain Fermichamp, and the selected strains also led to high glycerol levels and were able to almost completely consume glucose and fructose during fermentation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These authors concluded that commercial wine strains are characterized by high biomass concentration and good fermentative performance, low acetate production, and low ethyl butyrate synthesis. More recently, and similar to the work presented here for S. cerevisiae mezcal strains, Franco-Duarte et al [12] established that, for their 24 S. cerevisiae strains, ethanol and organic acids (in particular acetic acid) concentration explained most of the metabolic differences among strains. The S. cerevisiae strains studied in more detail here produce comparable amounts of ethanol as the commercial strain Fermichamp, and the selected strains also led to high glycerol levels and were able to almost completely consume glucose and fructose during fermentation.…”
Section: Discussionsupporting
confidence: 83%
“…In winemaking, the use of pure yeast cultures allows a better control of the fermentations; however, it can also reduce the production of some desired metabolites, both from the yeast's metabolism itself and from transformation of precursors present in the grape must. For this purpose, it is increasingly seen more convenient to use different yeast genera and species, which can contribute or influence the chemical composition and the flavor of wines [4,5,12,13,17,19,21]. The volatile compounds produced by the strains analyzed in this study are of great aromatic value, especially the production of ethyl hexanoate and ethyl octanoate (apple note), isoamyl acetate (banana note), and phenyl ethyl acetate (fruity, floral notes), compounds which could render (in the appropriate amounts) good organoleptic characteristics to a wine.…”
Section: Discussionmentioning
confidence: 99%
“…For instanace, a multi objective heuristic algorithm based on analytic hierarchy process has been introduced in clinical medicine to find a discriminatory subset of genes that help diagnose and treat cancer [28]. Another study adopts the existing algorithms to select significant features from combined multi scale and different origin data and use them in biotechnological applications such as strain selection in winemaking [29]. This paper focuses on classifying different crops using feature selection algorithms and comparing the results with that of using the existing spectral indices.…”
Section: Introductionmentioning
confidence: 99%
“…These results were somewhat expected, since yeasts used in laboratory applications undergo several mutations according to years and years of laboratory use, which leads to some adaptation and evolution. This was shown previously by several authors, but they focused only on nuclear genomic data [69][70][71][72][73][74][75]. Another important result was the separation, to some extent, of wine strains, which could justify an already adaptive evolution to a very specific biotechnological niche.…”
Section: Discussionmentioning
confidence: 60%